Testing a varying-A model for dark energy within co-varying physical couplings framework - Cuzinatto, R. R.; Gupta, R. P.; Holanda, R. F. L.; Jesus, J. F. [UNESP]; Pereira, S. H. [UNESP] (Oxford Univ Press, 2022)
The Co-varying Physical Couplings (CPC) framework is a modified gravity set up assuming Einstein Field Equations wherein the quantities {G, c, A} are promoted to space-time functions. Bianchi identity and the requirement of stress-energy tensor conservation entangle the possible variations of the couplings {G, c, A}, which are forced to co-vary as dictated by the General Constraint (GC). In this paper, we explore a cosmological model wherein G, c, and A are functions of the redshift respecting the GC of the CPC framework. We assume a linear parametrization of A in terms of the scale factor a. We use the ansatz G/G = sigma(c/c) with sigma = constant to deduce the functional forms of c = c(z) and G = G(z). We show that this varying-{G, c, A} model fits SNe Ia data and H(z) data with sigma = 3. The model parameters can be constrained to describe dark energy at the background level.
Keywords: Gravitation; Cosmological parameters; Cosmology: theory; Dark energy; Distance scale